Plant biotechnology: The genetic manipulation of plants - SLATER, ADRIAN; Scott, Nigel W. (New Delhi Oxford University Press, 2008)
Plant biotechnology: The genetic manipulation of plants
Plant biotechnology: The genetic manipulation of plants